AUDIT MUTU PENDIDIKAN ISLAM MELALUI SUPERVISI PEMBELAJARAN DI MTs NEGERI 1 KOTA PALEMBANG - Indra Mukti Abam; Saipul Annur; Asri Karolina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational quality assurance is a crucial strategy in ensuring the effectiveness of educational institutions, particularly in Islamic education such as madrasahs. Instructional supervision serves as a key instrument in quality auditing, as it functions to evaluate, guide, and improve the teaching and learning process. This study aims to analyze the implementation of Islamic education quality audits through instructional supervision at MTs Negeri 1 Palembang. This research employs a qualitative approach with a descriptive-analytical case study design. Informants were selected using purposive sampling, including the principal, vice principal of curriculum, and teachers. Data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that instructional supervision plays a significant role in improving teacher competence, teaching quality, and the effectiveness of educational management. Supervision is implemented systematically through planning, classroom observation, evaluation, and follow-up actions supported by digital systems. Furthermore, supervision encourages teacher reflection and instructional innovation. Therefore, quality auditing through instructional supervision is proven to be an effective strategy in enhancing the quality of Islamic education in a sustainable manner.